Protokolle des Ministerrates der Zweiten Republik der Republik Österreich, Kabinett Leopold Figl I, Band 8 (25. November 1947 bis 20. Jänner 1948) Kabinett Leopold Figl I 20. Dezember 1945 bis 8. November 1949 - Enderle-Burcel, Gertrude (Verlag der Österreichischen Akademie der Wissenschaften, 2017)
The Edition of the Minutes of the Cabinet Meetings Figl I constitutes an important contribution to research on the early years of Austria's Second Republic and the reconstruction and renewal of the state and its political components after World War II. The minutes of the cabinet meetings have to be regarded as central source materials on this early and complex phase of the Second Republic. Volume 8 of the Edition encompasses the minutes of meeting of November 25, 1947 to meeting of January 20, 1948.